A morphometric methodology to assess planktonic foraminiferal response to environmental perturbations: the case study of Oceanic Anoxic Event 2, Late Cretaceous - FALZONI, Francesca; PETRIZZO, Maria Rose; VALAGUSSA, Marco (Società Paleontologica Italiana, 2018)
Dwarfism of planktonic foraminiferal specimens is recognised across several intervals subject to globally extended environmental disturbances such as the Cretaceous/Palaeogene boundary and the latest Cenomanian-earliest Turonian Oceanic Anoxic Event 2 (OAE 2) in the Late Cretaceous. However, the occurrence of dwarfed specimens is generally based on the observation of a decrease in the size of specimens at the stereomicroscope without acquiring morphometric data. This approach prevents from assessing the inter-sample morphometric variation of species, reconstructing species-specific trends, and comparing data from different localities to extrapolate global from local signals. We present herein a first step toward the development of a morphometry-based methodology to assess planktonic foraminiferal response to past environmental perturbations. To perform this study, we selected OAE 2 as a target event and we focused on two species, Rotalipora cushmani (Morrow, 1934) and Whiteinella brittonensis (Loeblich & Tappan, 1961), commonly occurring in the assemblages and likely having different palaeoecological preferences. Specimens analysed are from Eastbourne (England), Clot Chevalier (SE France), and Tarfaya (core S57, Morocco). For both species, we measured selected shell parameters (i.e., the number of chambers in the last whorl, the maximum diameter and the height of the test). Our study suggests that the maximum diameter across the first chamber of the inner whorl visible in spiral view is the simplest and most objective methodology to estimate shell size variation in trochospiral planktonic foraminifera, and that this morphometric parameter is likely the most sensitive to the Cenomanian-Turonian environmental disturbances, and thus its variability through time appears worth investigating across other key-stratigraphic intervals. Moreover, this study indicates that the acquisition of morphometric data is required to accurately reconstruct planktonic foraminiferal response to environmental perturbations, because ...